Evaluation of hemostatic effect of polyelectrolyte complex-based dressings. (November 2017) - Buriuli, Manisha; Kumari, Wasupalli Geeta; Verma, Devendra
The aim of this work was to develop a polyelectrolyte complex-based hemostatic dressing made from chitosan and polygalacturonic acid. Porous dressings were fabricated by ultrasonication of chitosan and alginate solutions followed by freeze-drying. Since chitosan has inherent hemostatic properties, and polygalacturonic acid is anti-inflammatory in nature, it was desired to combine these two polymers to develop an effective hemostatic dressing, which may also promote wound healing. Porous structure of the bandages was observed using field-emission scanning electron microscope. Blood clotting behavior was studied using whole blood clotting assay. Plasma recalcification time, prothrombin time, and activated partial thromboplastin time were also determined to study the mechanism of clotting. The dressings were found to accelerate clotting rates and showed increased thrombin activity with an increase in chitosan concentration.